ANALISIS PENGARUH PENDIDIKAN MULTIKULTURAL TERHADAP SIKAP SOSIAL DAN EMPATI SISWA SEKOLAH DASAR - Muhammad Azman; Norma Hidayatussholikhah; Muhammad Syaikon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Multicultural education is understood as an educational approach that positions cultural, religious, ethnic, linguistic, and social diversity of learners as a social reality that must be acknowledged, respected, and constructively managed within the learning process. In the context of Indonesia, which is characterized by a highly multicultural society, multicultural education holds a strategic role in shaping students’ character from the primary education level, particularly in fostering social attitudes and empathy. This article aims to comprehensively examine the influence of multicultural education on the social attitudes and empathy of elementary school students through a literature review approach. The method employed is a literature study by analyzing relevant national and international journal articles published between 2015 and 2025. The review process includes source identification, article selection based on specific criteria, evaluation of research quality, and synthesis of research findings. The results of the review indicate that the implementation of multicultural education contributes significantly to the improvement of students’ social attitudes, including tolerance, cooperation skills, social awareness, and respect for differences. Furthermore, multicultural education has been shown to be effective in enhancing students’ empathy through learning activities that emphasize respect for diversity, cross-cultural social interactions, and reflective learning experiences. The integration of multicultural values into elementary school learning also contributes to the creation of an inclusive classroom climate that supports students’ social-emotional development. Therefore, multicultural education needs to be implemented in a planned, systematic, and sustainable manner within the curriculum and instructional practices of elementary schools.